High Frequency of Dermatological Complications in Children and Adolescents with Type 1 Diabetes: A Web-Based Survey. (November 2021) - Lombardo, Fortunato; Passanisi, Stefano; Tinti, Davide; Messina, Maria Francesca; Salzano, Giuseppina; Rabbone, Ivana
Introduction: Despite advances in the management of type 1 diabetes (T1D), there is an increasing incidence of skin reactions related to diabetes devices such as patch pumps and glucose sensors. Aim of the present study was to assess the prevalence of dermatological complications in pediatric patients with T1D using technological devices. Methods: Online survey regarding skin reactions related to the use of patch pumps and/or glucose sensors was administered to families of children and adolescents (0-17 years) with T1D. Data were collected on demographic characteristics, duration of diabetes, and clinical features of dermatological complications if present. Results: Our study population consisted of 139 patients (female 51.8%) aged 11.1 ± 3.3 years. More than half (51.1%) experienced skin reactions due to patch pumps or glucose sensors. Dermatological complications were mainly caused by continuous glucose monitoring (56.3% of total). Timing of appearance of dermatological reactions varied from a few days to several months after the introduction of the device. The application of hypoallergenic barrier bandages was the most frequently adopted measure to solve the issue. Conclusions: Our study confirmed high frequency of dermatological complications among pediatric patients with type 1 diabetes. Well-designed studies are awaited to provide clear recommendations to minimize the burden of skin issues related to technological devices.